Responder
Here are the factored forms of the given expressions:
1. \(25a^{2} - 16 = (5a - 4)(5a + 4)\)
2. \(2a^{2} + 2b^{2} = 2(a^{2} + b^{2})\)
3. \(x^{2}y^{2} - 1 = (xy - 1)(xy + 1)\)
4. \(28x^{3} - 63xb^{2} = 7x(2x - 3b)(2x + 3b)\)
5. \((2x + 3y)^{2} - 9 = (2x + 3y - 3)(2x + 3y + 3)\)
6. \(4x^{2} - (3x - 2y)^{2} = (-x + 2y)(5x - 2y)\)
7. \(25a^{2}(a - 3b) + 9(3b - a) = (a - 3b)(5a - 3)(5a + 3)\)
If you need further explanation on any of these, feel free to ask!
Solución
Certainly! Let's factor each of the given expressions step by step.
---
**1. \( 25a^{2} - 16 \)**
This is a **difference of squares**:
\[
25a^{2} - 16 = (5a)^{2} - 4^{2} = (5a - 4)(5a + 4)
\]
---
**3. \( 2a^{2} + 2b^{2} \)**
Factor out the common term **2**:
\[
2a^{2} + 2b^{2} = 2(a^{2} + b^{2})
\]
*Note:* \(a^{2} + b^{2}\) cannot be factored further over the real numbers.
---
**5. \( x^{2}y^{2} - 1 \)**
This is another **difference of squares**:
\[
x^{2}y^{2} - 1 = (xy)^{2} - 1^{2} = (xy - 1)(xy + 1)
\]
---
**7. \( 28x^{3} - 63xb^{2} \)**
First, factor out the greatest common factor **7x**:
\[
28x^{3} - 63xb^{2} = 7x(4x^{2} - 9b^{2})
\]
Notice that \(4x^{2} - 9b^{2}\) is a **difference of squares**:
\[
4x^{2} - 9b^{2} = (2x)^{2} - (3b)^{2} = (2x - 3b)(2x + 3b)
\]
So, the fully factored form is:
\[
28x^{3} - 63xb^{2} = 7x(2x - 3b)(2x + 3b)
\]
---
**9. \( (2x + 3y)^{2} - 9 \)**
This is a **difference of squares**:
\[
(2x + 3y)^{2} - 3^{2} = (2x + 3y - 3)(2x + 3y + 3)
\]
---
**11. \( 4x^{2} - (3x - 2y)^{2} \)**
Again, a **difference of squares**:
\[
4x^{2} - (3x - 2y)^{2} = (2x)^{2} - (3x - 2y)^{2} = [2x - (3x - 2y)][2x + (3x - 2y)]
\]
Simplify each binomial:
\[
[2x - 3x + 2y][2x + 3x - 2y] = (-x + 2y)(5x - 2y)
\]
*Alternatively written as:*
\[
(2y - x)(5x - 2y)
\]
---
**13. \( 25a^{2}(a - 3b) + 9(3b - a) \)**
First, notice that \(9(3b - a) = -9(a - 3b)\). Factor out \((a - 3b)\):
\[
25a^{2}(a - 3b) - 9(a - 3b) = (a - 3b)(25a^{2} - 9)
\]
Now, factor \(25a^{2} - 9\) as a **difference of squares**:
\[
25a^{2} - 9 = (5a)^{2} - 3^{2} = (5a - 3)(5a + 3)
\]
So, the fully factored form is:
\[
25a^{2}(a - 3b) + 9(3b - a) = (a - 3b)(5a - 3)(5a + 3)
\]
---
**Summary of Factored Forms:**
1. \(25a^{2} - 16 = (5a - 4)(5a + 4)\)
3. \(2a^{2} + 2b^{2} = 2(a^{2} + b^{2})\)
5. \(x^{2}y^{2} - 1 = (xy - 1)(xy + 1)\)
7. \(28x^{3} - 63xb^{2} = 7x(2x - 3b)(2x + 3b)\)
9. \((2x + 3y)^{2} - 9 = (2x + 3y - 3)(2x + 3y + 3)\)
11. \(4x^{2} - (3x - 2y)^{2} = (-x + 2y)(5x - 2y)\)
13. \(25a^{2}(a - 3b) + 9(3b - a) = (a - 3b)(5a - 3)(5a + 3)\)
---
If you have any specific questions about these factorizations or need further assistance, feel free to ask!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución